Metodologias ativas de ensino aplicadas às engenharias nas World-Class Universities classificadas no Times Higher Education World University Ranking - Cordeiro, Luiz Gustavo (2021)
This research aims to identify the Active Methodologies (MA) of teaching used in the engineering courses of the World-Class Universities (WCU) classified among the 15 best in the Teaching indicator of the Times Higher Education World Universities (THE-WU) ranking, in the period of 2011 to 2020. For this it was necessary to first identify in the literature the main references and concepts referring to what defines WCU, using the theories proposed by Deetz (1996) on discourse analysis through the contrasting dimensions of the representational practices' metatheory, which divides the theoretical bases of the authors according to the origin of their problems and the objective of their study. In a second step, in order to establish the sample for data collection, the 15 best WCU classified in the THE-WU ranking were identified in the period between 2011 and 2020, in the specific teaching indicator, analyzing the ten editions of the rankings regarding oscillation and overall average of WCU ratings. Then, the MAs used in engineering programs in the last five years were identified in the literature through a systematic literature review. Once these steps were met, the research searched the institutional teaching menus and pages of the 15 selected WCU, in order to identify the application of active methodologies, either implicitly or explicitly, then classifying them according to their incidence. The research showed the application of MA in all the selected WCU, there was also a low disparity between the MA evidenced in the literature review and in the WCU documents, except for the “Design Thinking” methodology, which was evidenced in practice, but not in theory. And the MA “Flexible Classroom” that was evidenced during the systematic literature review, but not during the documentary analysis. It was also possible to identify the concomitant application of different MAs, analyzing the number of other MAs that each one relates to and the frequency that such relationship occurs. It was also noticed through the analyses, a series of standards of the application of the MA as the “Learning by Doing” methodology has greater application in laboratory classes; "Collaborative Teaching" and "Project-Based Learning" are commonly applied in classes that involve prototyping and design; “Inverted Classroom” applies to classes that involve knowledge of the humanities or ethics; “Community of Practices” relates to courses that involve studies of sustainability, society and development; “Problem-Based Learning” is applied in introductory and analytical disciplines and “Role-playing” is usually applied in disciplines that instigate creativity. Finally, the main Active Methodologies were identified according to the research objective, respectively, Project-Based Learning, Hybrid Teaching, Learning by Doing, Collaborative Teaching, Problem-Based Learning, E-learning, the Classroom inverted, Design Thinking, Gamification, Roleplaying and Communities of Practice.